Sistematización de mi experiencia como maestro artista en la puesta en escena: Un Beso De Dick, obra del teatro colombiano con enfoque en el respeto por la diversidad sexual y de género (2023)
The present thesis aims to document the process experienced through participation as a performer in the staging of 'Un beso de Dick,' a play in Colombian theater based on the book by Bogotá writer Fernando Molano. This production emphasizes respect for sexual and gender diversity. The thesis intends to create a reflective account of the experiences of the teacher, artist in training, and other participants involved in the play, including actors, actresses, and the director of the latest seasons of the performance. The ultimate goal is to generate pedagogical strategies contributing to the creation of theatrical productions focusing on sexual and gender diversity. Consequently, this contributes to the visibility and advocacy for LGBTQ+ individuals within Antonio Nariño University and society.